Target Fixation Technique in State Plan a Critique Government of Karnataka - Planning Commission (Planning Commission, 1987)
Planning process which began three-and-a-half decades ago has undergone and evolution incorporating new dimensions into the exercises and hence to the development path chalked out. This, is true in the context of both national and state level planning. One of the unique features of this evolution is the increasing degree of disaggregation attempted-disaggregation in terms of sector and space dimensions In Karnataka, one finds distinctly discernible five levels of hierarchy covered in the plan exercise, namely, state's economy, sector, sub-sector, programme and scheme. Targets in physical and/or monetary terms are fixed for variables covering these various levels.
Perspective Planning Division Planning Department, Government of Karnataka